Addressing the challenges of overweight and obesity: strategies for promoting a healthier future - Chaudhuri, Irfan; Islam, Md. Shahidul (Intelektual Pustaka Media Utama, 2025)
The prevalence of overweight and obesity among over 1 billion people worldwide constitutes a major public health concern. There is an increased risk for the onset of noncommunicable diseases such as type 2 diabetes, cardiovascular diseases, and various types of cancer, while productivity and life quality are diminished. The social, environmental, and behavioral influences on obesity and overweight can be mitigated through targeted interventions, as these conditions are largely avoidable. This study explores the latest findings on the causes, consequences, and remedies for overweight and obesity, with a global perspective. Additionally, it outlines several effective measures and strategies that have been put into place or are being considered in various contexts, including financial constraints, marketing limits, primary healthcare options, and school-based initiatives. To change the obesity epidemic and promote healthy eating and active living for everyone, the research calls for immediate action and a useful strategy that promotes healthy eating and diet, increased physical exercise, and modifications to environmental elements.